The influence of entrepreneurial spirit on sports culture construction from the perspective of cognitive regulation - Pang, Bo; Liu, Hao; Liu, Zhongqiang (Frontiers in Psychology, 2022)
The purposes of this study are to extract the essence from the in-depth study of entrepreneurial spirit and the exploration of China's sports culture construction, find out the beneficial parts in line with China's sports culture construction, and put forward operational suggestions and countermeasures for dealing with the relationship between entrepreneurial spirit and sports culture to help China's sports culture construction move towards a new level. This exploration discusses the influence of entrepreneurial spirit on sports culture from the perspective of cognitive regulation, and explores the importance of entrepreneurial spirit from the aspects of social psychology, system, economy, and ethics. The structure of sports culture is analyzed, and the role of entrepreneurial spirit in promoting the construction of sports culture is expounded. Moreover, a questionnaire survey is conducted to investigate the impact of entrepreneurial spirit on the construction of sports culture from the cognitive regulation perspective. The results show that most people agree with the development of the entrepreneurial spirit and positively impact the promotion of entrepreneurial spirit. Most people are not satisfied with the attention and level of sports culture construction. In China's sports culture, the proportion of the entrepreneurial spirit is still tiny. Thereby, entrepreneurial spirit education must be vigorously promoted to enhance the integration of entrepreneurial spirit and sports culture. The entrepreneurial spirit needs to be introduced in the construction of sports culture. It is essential to do a good job in promoting entrepreneurial spirit, improving the supporting facilities related to sports culture and strengthening the correlation between sports culture and the entrepreneurial spirit. By discussing the influence of entrepreneurial spirit on sports culture, this exploration puts forward relevant opinions for developing sports culture. It is expected that they can have some reference values. This exploration provides new ideas for promoting the combination of sports culture construction and the dissemination of entrepreneurial spirit, which has crucial theoretical and practical significance.